Infirādātul Imām Abī Ja’far Al-Madanī Fī Bābil Asma’ Fī Farsyi Hurūfil Qurānul Karīm Min Ṭorīq Toyyibatin Nasyr Fil Qirā`ātil ‘Asyr Sūraħ Al-Baqaraħ Wa Āli ‘Imrān Namūdzajan: انفرادات الإمام أبي جعفر المدني في باب الأسماء في فرش حروف القرآن الكريم من طريق طيبة النشر في القراءات العشر سورة البقرة وآل عمران نموذجا - Heggy Fajrianto Herman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
The purpose of this study is to find out what exactly is the cause of imam Abu Ja'far's independence in the recitation of the Qur'an. The author uses the method of analysis and through literature studies, namely by collecting valid data and those that have a relationship with the title of this journal, more specifically than books related to qira'at science. Some of the results of research from this journal are that taujih is a search for postulates about the reading of qira'at that exist by adhering to the postulates of the Qur'an, arabic language science, arabic accent, hadiths of the prophet, or Arabic verses and others from existing postulates. As for infirād (independence) it is a way of reading the quran that is in one of the 10 Imam qiroat which is different from the readings of other Imams both in terms of his ushul (his rules) and in terms of his farsy (which is not a rule).